Música no alívio da dor e da ansiedade durante a injeção intravítrea: ensaio clínico randomizado - Santos, Moniery da Silva (2022)
Introduction: ophthalmic procedures are characterized by being nociceptive, which can cause pain and anxiety. Intravitreal injection (IVI) is the treatment of choice for retinal diseases and a painful procedure, performed only under local anesthesia. One of the alternatives to treat pain is the use of non-pharmacological methods, such as music, for pain and anxiety relief, which have been investigated in several clinical settings. Objective: to evaluate the effect of music in relieving pain and anxiety in participants undergoing IVI. Method: controlled, randomized and blind trial, which was developed in a private ophthalmological clinic in Aracaju (SE), Northeast Brazil. The following were included in the survey: people aged 18 years or over; who underwent IVI for the treatment of diabetic macular edema, age-related macular degeneration, or central retinal vein occlusion. Participants were divided into two groups: control (CG), in which standard analgesia was available and there was no musical intervention; and experimental (EG), which in addition to standard analgesia, listening to music was administered according to the patient's preference, remaining during the entire procedure. Randomization was performed using opaque, sealed, and sequentially numbered envelopes. The main outcomes of the study were pain and anxiety, measured using the Numeric Verbal Scale (ranging from 0 to 10, with 0 being minimal pain and 10 being maximum pain) and the State-Trait Anxiety Inventory, respectively. The research was approved by the Ethics and Research Committee of the Federal University of Sergipe. Categorical variables were described using raw frequencies and percentages, and continuous variables using mean and standard deviation or median and interquartile range. The hypothesis of independence between categorical variables was tested using Fisher's Exact or Pearson's Chi-Square tests. The hypothesis of adherence of continuous variables to normal distribution was tested using the Shapiro-Wilk test. The hypothesis of equality of means or medians was tested in a context of repeated measures using ANOVA. The significance level adopted was 5% and the software used was R Core Team 2022 (Version 4.2.0). Results: the sample was homogeneously distributed between the groups in terms of baseline characteristics, consisting of 52 participants, predominantly men (63.5%), with a mean age of 62.7±8.2 years, who had type 2 diabetes mellitus (94.2%). More than half (59.6%) needed to receive IVI application due to the diagnosis of diabetic retinopathy. Before and after the procedure, participants reported no pain. Already at the time of insertion of the needle, mild pain was reported. Referred pain was different between groups when performing IVI (EG: 0 [0- 3]; GC: 0.5; p-value: 0.652). Anxiety was considered mild before (EG: 28 [35-34]; GC: 28 [24- 37]) and after (EG: 24 [22-27]; GC: 24 [22-27]; p-value: 0.993) the procedure in both groups. Conclusion: The association between standard analgesia and the patient's free choice of music is not superior to the isolated use of standard analgesia for the relief of pain and anxiety related to IVI. It is possible to reinforce the importance of studies that evaluate and detail the methods for alleviating these outcomes.